Emotional dysregulation as a part of the autism spectrum continuum: a literature review from late childhood to adulthood - Dell’Osso, Liliana; Massoni, Leonardo; Battaglini, Simone; De Felice, Chiara; Nardi, Benedetta; Amatori, Giulia; Cremone, Ivan Mirko; Carpita, Barbara (Frontiers in Psychiatry, 2023)
The concept of emotional dysregulation (ED) has recently gained interest in the scientific literature and is commonly defined as the inability to use the modulatory mechanisms involved in emotion regulation, resulting in a functioning meaningfully below the baseline. Even though the data available are still limited, an increasing number of studies have hypothesized a promoting role for some of the core features of autism spectrum disorder (ASD) in the development of ED, in particular being repetitive behaviors, social difficulties and alexythimia. In this framework, the purpose of this study was to review the literature that is currently available about presence and correlates of ED in young adults with autism spectrum conditions as well as to offer some insights about possible implications for illness trajectories. The data reported seems to point to a shared etiology between ED and repetitive/restricted ASD symptoms, with perseveration features serving as the foundation for the inability to control one’s emotions. In this context, a neurodevelopmental basis for ED could be consistent with the transnosographic conceptualization of ASD, which hypothesizes a potential neurodevelopmental basis for several psychiatric disorders, whose autistic traits would be the phenotypical presentation.